Cardiopulmonary effects of butorphanol in sevoflurane-anesthetized guineafowl (Numida meleagris) - Escobar, Andre [UNESP]; Valadao, Carlos A. A. [UNESP]; Brosnan, Robert J.; Flores, Fabiola N. [UNESP]; Lopes, Maristela C. S. [UNESP]; Gava, Fabio N. [UNESP] (Wiley-Blackwell, 2014)
Objective To evaluate the cardiopulmonary changes induced by intravenous butorphanol administration in guineafowl anesthetized with sevoflurane. Study design Prospective experimental trial. Animals Eight adult guineafowl (Numida meleagris) weighing 1.61 +/- 0.49kg were used for the study. Methods Birds were anesthetized with sevoflurane and allowed to breathe spontaneously. After endotracheal intubation, end-tidal sevoflurane was adjusted to 1.0 individual sevoflurane MAC that was previously determined in triplicate using a standard bracketing technique. The brachial artery was catheterized for direct pressure measurement and blood sampling. Heart rate and rhythm were monitored by electrocardiography and respiratory rate was recorded. Baseline data were recorded 30minutes after induction. Then, end-tidal sevoflurane was adjusted to 0.8 individual MAC and after 15minutes physiologic variables were measured again. Subsequently, butorphanol (4mgkg-1) was administered intravenously over 10seconds and physiologic responses were recorded at 1, 5, 10, 15, 20, 30 and 45minutes after administration. Results Butorphanol administration was associated with arrhythmias in all birds, including second-degree atrioventricular block, sinus arrest, ventricular and supraventricular tachycardia and ventricular premature complexes. Heart rate and arterial blood pressures decreased significantly 1minute after butorphanol administration. Two birds developed severe hypotension, apnea and ventricular fibrillation 5minutes after administration, and one died. Conclusions and clinical relevance The butorphanol dose (4mgkg-1) that produces clinically relevant sevoflurane MAC reduction in guineafowl caused severe adverse cardiopulmonary effects in two birds and was considered unsafe under the conditions used in this study.
Keywords: Anesthesia; birds; butorphanol; cardiac arrhythmias; monitoring; Sevoflurane